The Factors Affecting Audit Judgment - Irawati, Sheila Anatasia; Solikhah, Badingatus (Accounting Analysis Journal, 2018)
The purpose of this research are analyze and to find out influence of audit situation, gender, audit fee, task complexity, due professional care, and framing on audit judgment. The population of this study was Two hundred-fifty-seven auditors who work at KAP Semarang City and register in Indonesian Institute of Certified Public Accountants (IICPA). Sampling method in this research uses non probability and convenience sampling technique, Sixty-nine as respondents from auditors who work at Nine KAP Semarang City, but only Twenty-three respondents for instrument test and Forty-six respondents use as research sample. Collection of data in this research uses primary data from distribution questionnaire. Methods of data analysis is multiple linear regression using IBM SPSS 24 statistical software. Based on the results of this study, it can be concluded that the audit situation, due professional care, and framing have a positive and significant impact on audit judgment. However, gender, audit fees, and task complexity have no significant effect on audit judgment. The conclusions of this research, some factors can affect on audit judgment there are audit situation, due professional care, and framing. However, some factors cannot affect on audit judgment there are gender, audit fee, and task complexity.